Adolf Beck (1877-1904) - Beck, Adolph; Watson, Eric R., 1879?-1927 (Notable British trials series., 1924)
A case of mistaken identity in which Beck was tried in the Old Bailey for larceny, 1896, convicted, served five years in prison, was again indicted and convicted in 1904. Sentence was suspended and a court of inquiry appointed, which reported that all charges against Beck in both trials were absolutely without foundation.